Cholesterol‐sensing liver X receptors stimulate Th2‐driven allergic eosinophilic asthma in mice. Issue 3 (2nd August 2016) - Smet, Muriel; Van Hoecke, Lien; De Beuckelaer, Ans; Vander Beken, Seppe; Naessens, Thomas; Vergote, Karl; Willart, Monique; Lambrecht, Bart N.; Gustafsson, Jan‐Åke; Steffensen, Knut R.; Grooten, Johan
Abstract: Introduction: Liver X receptors (LXRs) are nuclear receptors that function as cholesterol sensors and regulate cholesterol homeostasis. High cholesterol has been recognized as a risk factor in asthma; however, the mechanism of this linkage is not known. Methods: To explore the importance of cholesterol homeostasis for asthma, we investigated the contribution of LXR activity in an ovalbumin‐ and a house dust mite‐driven eosinophilic asthma mouse model. Results: In both models, airway inflammation, airway hyper‐reactivity, and goblet cell hyperplasia were reduced in mice deficient for both LXRα and LXRβ isoforms (LXRα −/− β −/− ) as compared to wild‐type mice. Inversely, treatment with the LXR agonist GW3965 showed increased eosinophilic airway inflammation. LXR activity contributed to airway inflammation through promotion of type 2 cytokine production as LXRα −/− β −/− mice showed strongly reduced protein levels of IL‐5 and IL‐13 in the lungs as well as reduced expression of these cytokines by CD4 + lung cells and lung‐draining lymph node cells. In line herewith, LXR activation resulted in increased type 2 cytokine production by the lung‐draining lymph node cells. Conclusions: In conclusion, our study demonstrates that the cholesterol regulator LXR acts as a positive regulator of eosinophilic asthma in mice, contributing to airway inflammation through regulation of type 2 cytokine production. Abstract : Our study demonstrates that the cholesterol regulator LXR acts as a positive regulator of allergic eosinophilic asthma in mice, contributing to airway inflammation through regulation of type 2 cytokine production.